An Analysis on Students’ Errors in Using Conditional Sentences Type II on Third Grade of SMA N 8 Jambi - Septa Riani; Yanti Ismiyati (JELT: Journal of English Language Teaching, 2020)
The purpose of this study was to analyze and to classify the types of errors, to find the frequency of errors in each type in class 3 IPS SMAN 8 Jambi City. The method used in this research is qualitative method. qualitative design applied in research in the form of case studies. This research was also carried out using error analysis procedures ranging from data collection, error identification, error translation and problem explanation. in this study, the data can be through observations and test. The results showed that students made four types of errors namely omission, addition to misformation and misoder of the four errors, the most errors lie in misformation. there are as many as 50,94%. further note that 24,52% occurs in addition and 24,52% occurs in omission. while misoder is 0%Keyword: Error Analysis, Conditional Sentences Type II